2021
DOI: 10.1101/2021.03.31.437984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplexed 3D atlas of state transitions and immune interactions in colorectal cancer

Abstract: Advanced solid cancers are complex assemblies of tumor, immune, and stromal cells that invade adjacent tissue and spread to distant sites. Here we use highly multiplexed tissue imaging, spatial statistics, and machine learning to identify cell types and states underlying morphological features of known diagnostic and prognostic significance in colorectal cancer. We find that a thorough spatial analysis requires imaging the entire tumor region, not small fields of view (e.g. those found in tissue microarrays). … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 118 publications
(195 reference statements)
0
40
0
Order By: Relevance
“…The resulting molecular and morphological data were then analyzed with respect to histopathology annotations. CyCIF and H&E imaging were performed on whole slides, not tissue microarrays (TMAs) or small fields of view (FOVs) (Baharlou et al, 2019), to preserve the spatial relationships of different histologies and to provide sufficient statistical power (Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting molecular and morphological data were then analyzed with respect to histopathology annotations. CyCIF and H&E imaging were performed on whole slides, not tissue microarrays (TMAs) or small fields of view (FOVs) (Baharlou et al, 2019), to preserve the spatial relationships of different histologies and to provide sufficient statistical power (Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analyses including single-cell genomic and proteomic approaches can yield important insights into the heterogeneous cell states within tumors. These methods typically employ tissue-dissociative methods which eliminate the spatial associations between tumor cells and other components of the tumor microenvironment thereby preventing the evaluation of tissuelevel phenomena which can be critical for promoting tumorigenesis [15][16][17] . An important recent study using dissociative methodologies identified a distinct population of tumor-infiltrating macrophages that express CD73 in glioblastoma 33 ; these cells may persist through recurrence and promote resistance to immunotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Given cell-state specific expression of critical purinergic regulators such as CD73 and CD39, we next sought to explore the expression, spatial organization, and cell-cell interactions of these proteins in native tissue at sub-cellular resolution. Unlike dissociated scRNA-seq, multiplexed tissue imaging preserves spatial relationships between cells and proteins, enabling correlation of molecular states and tissue architecture 13,15 .…”
Section: Multiplexed Single Cell Analysis Of Glioblastoma Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in tumors, cancer cells exist in proliferative, non-proliferative, and arrested states 11 . In addition, many cells in tumor masses are not neoplastic, but rather are immune and stromal cells 12 that are non-uniformly distributed across the tumor 13 . The crosstalk between distinct cellular components of the tumor ecosystem creates local conditions that may either promote or inhibit cell proliferation 14 .…”
mentioning
confidence: 99%